Utilization of Waste Materials (GGBS+FLY ASH) In Concrete - Akansha Gautam; Anita Chaturvedi; Lokesh Singh (International Journal of Scientific Research in Civil Engineering, 2024)
Concrete is an extensively used material in the construction industry. Normally the concrete is made up of cement, sand and coarse aggregate at the appropriate ratio as per the requirements. The cement used in the preparation of concrete has its own detrimental effect on health and the environment. Sand is a natural building material that depletes fast due to excessive usage. Sand mining done for construction purposes has its own impact on the environment. As a result, a concentrated effort has been made to use alternative technologies to replace cement and sand. As such, the main goal of this research is to suggest alternative approaches to address the issues of excessive sand utilization by agricultural wastes and industrial wastes and by-products.